PENGARUH KECERDASAN SPRITUAL, KECERDASAN INTELEKTUAL, DAN KECERDASAN EMOSIONAL TERHADAP KINERJA GURU DI SMP ISLAM ATHIRAH 1 MAKASSAR - Nilamartini, Nilamartini; Syamsuri, Andi Sukri; Jusriadi, Edi (COMPETITIVENESS, 2021)
The purpose of this research is to know and analyze the influence of spritual, intellectual and emotional intelligence on the performance of teachers of Smp Islam Athirah 1 Makassar and to know and analyze the variables that have the dominant effect. This research uses quantitative research. The population in this study was a teacher of SMP Islam Athirah 1 Makassar, a population of 31 people. Sample withdrawal techniques are saturated samples or total sampling. The instruments used in this study were questionnaires then processed using SPSS 21.0 program by descriptive analysis, data validation and reliability test, and multiple regression test which includes partial test (t test) and simultaneous test (F test). The results showed that spritual intelligence has a significant positive effect on teacher performance, intellectual intelligence has a significant negative effect on teacher performance, emotional intelligence has a positive and significant effect on teacher performance, spritual intelligence has a dominant effect on teacher performance compared to variable intellectual intelligence and emotional intelligence. Keywords: spritual intelligence, intellectual intelligence, emotional intelligence and performance